Batteries: Nanoscale Heterogeneity of Multilayered Si Anodes with Embedded Nanoparticle Scaffolds for Li‐Ion Batteries (Adv. Sci. 10/2017). Issue 10 (17th October 2017) - Haro, Marta; Singh, Vidyadhar; Steinhauer, Stephan; Toulkeridou, Evropi; Grammatikopoulos, Panagiotis; Sowwan, Mukhles
Abstract : A versatile synthesis approach is proposed for Li‐ion battery anodes composed by intercalated layers of amorphous‐Si thin films and Ta nanoparticles by Mukhles Sowwan and co‐workers in article number1700180 . The porosity, nanomechanical, and electrochemical properties of the Si layers are dictated by the Ta nanoparticle scaffolds, leading to anodes with enhanced charge‐discharge rate and self‐limited capacity. The proposed prototype meets the advantages of nano‐ and thin film technologies.